MERKEL, Á., Libertad. Memorias (1954-2021), RBA, Barcelona, 2024, 831 pp. - Romero Bartumeus, Luis (PEACE & SECURITY-PAIX ET SÉCURITÉ INTERNATIONALES (EuroMediterranean Journal of International Law and International Relations), 2025)
Reseña de: MERKEL, Á., Libertad. Memorias (1954-2021), RBA, Barcelona, 2024, 831 pp.